THE USE OF WEB-BASED APPLICATIONS ON POSYANDU CADRE KNOWLEDGE ABOUT EARLY DETECTION STUNTING - Pratiwi, Putu Irma; Ayu Desy Sekarini, Ni Nyoman (Jurnal Kesehatan Al-Irsyad, 2021)
Stunting remains a major health problem worldwide. Although its global prevalence is slowly decreasing. Stunting in infancy and childhood can lead to increased morbidity, poor childhood education, short status in adulthood. Posyandu is used to overcome stunting problems. One of the current innovations is the use of information technology. Smartphones have become a necessity for modern society, it is very possible to be used as a medium for socializing early detection of stunting and monitoring the nutritional status of children. The research objective was to determine the use of web-based applications on posyandu cadres' knowledge of early stunting detection. The research design used a pre-experimental method using one group pretest posttest design. The sampling technique in this study was total sampling. The research location is in Tegallinggah Village, Buleleng Regency. The analysis technique used the Paired T Test with a 95% confidence interval and a p value <0.05. The results of using a Web-based application have an effect on increasing the knowledge of posyandu cadres on early detection of stunting, the significance value is 0.000, which is smaller than p 0.05, this means that there is a significant difference in the knowledge of posyandu cadres before the intervention and after the intervention is given. Keywords: Web-based application, Knowledge, Early detection of stunting, Posyandu cadres